2019
DOI: 10.2147/jpr.s191860
|View full text |Cite
|
Sign up to set email alerts
|

<p>Activation of hippocampal microglia in a murine model of cancer-induced pain</p>

Abstract: IntroductionPain is a common and debilitating comorbidity of metastatic breast cancer. The hippocampus has been implicated in nociceptive processing, particularly relating to the subjective aspect of pain. Here, a syngeneic mouse model was used to characterize the effects of peripheral tumors on hippocampal microglial activation in relation to cancer-induced pain (CIP).Materials and methodsMice were systemically treated with the colony-stimulating factor 1 receptor inhibitor Pexidartinib prior to intrafemoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…The hippocampus is one of the key brain regions in pain signals modulating [15], particularly with respect to the affective aspect of pain perception [16,17] and abnormal emotional processes, including anxiety and depression [18]. Accumulating studies have suggested that chronic pain arising from peripheral nerve injury induces alterations in different areas of the brain including impaired hippocampal mossy fiber-CA3 synaptic plasticity and DG neurogenesis [19][20][21].…”
Section: Ivyspringmentioning
confidence: 99%
“…The hippocampus is one of the key brain regions in pain signals modulating [15], particularly with respect to the affective aspect of pain perception [16,17] and abnormal emotional processes, including anxiety and depression [18]. Accumulating studies have suggested that chronic pain arising from peripheral nerve injury induces alterations in different areas of the brain including impaired hippocampal mossy fiber-CA3 synaptic plasticity and DG neurogenesis [19][20][21].…”
Section: Ivyspringmentioning
confidence: 99%
“…The pathological features of the hippocampal tissues were observed using an automated quantitative pathology imaging system (Leica, Wetzlar, Germany). H&E staining was performed as previously described [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described [ 27 , 29 , 30 ]. The sectioned tissues were deparaffinized in a dry oven at 60 °C and then rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…CPP, open field activity, flinching, guarding, weight bearing, gait analysis, vocalizations, burrowing (King et al, 2007;King et al, 2008;Ungard et al, 2014;Slosky et al, 2016;Gdowski et al, 2017;Remeniuk et al, 2018;Zhang et al, 2018;Buehlmann et al, 2019;Miladinovic et al, 2019;Sliepen et al,…”
Section: ) Spontaneousmentioning
confidence: 99%